Impact of myocardial injury on cardiovascular complications in hospitalized patients with COVID-19: insights from Latin America - Cárdenas-Marín, Paula Andrea; Cordoba-Melo, Brayan Daniel; Carrillo-Gómez, Diana Cristina; León-Giraldo, Hoover; Mendoza, Iván; Flórez, Noel; Larrea Gómez, Ricardo Enrique; Mercedes, Jessica Mirella; Herrera, Cesar J.; Lugo-Peña, Julián; Cárdenas-Aldaz, Liliana Patricia; Rossel, Victor; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionViral infection by SARS-CoV2 is a pandemic affecting over 600 million people worldwide. One of five hospitalized patients may present myocardial injury, strongly associated with disease severity and mortality.MethodologyRetrospective cross-sectional study of hospitalized COVID-19 patients diagnosed between May 01, 2020, and June 30, 2021, from the database of the Registro Latinoamericano de Enfermedad Cardiovascular y COVID-19 (CARDIO COVID 19–20) with a troponin value recorded during hospitalization. A descriptive analysis of sociodemographic and clinical characteristics was performed. Bivariate analysis was conducted according to the presence or absence of myocardial injury. Survival analysis was made using Kaplan–Meier curves, by the presence of myocardial injury. A multivariate Poisson regression model was performed to determine factors associated with mortality. Statistical analyses were performed using the RStudio V.1.4.1717 package.ResultsA total of 2,134 patients were included, 64.2% were male, and 911 patients had myocardial injury. The median age of the total population was 61 years. Individuals with myocardial injury had a higher prevalence of hypertension, diabetes, and dyslipidemia. Survival probability was lower in this subgroup. Patients with myocardial injury had a 1.95 times higher risk of death. Age, male sex, chronic kidney disease, arrhythmias, decompensated heart failure, requirement of inotropic/vasopressor, and invasive mechanical ventilation were related to higher mortality risk in patients with myocardial injury.ConclusionPatients with COVID-19 and myocardial injury exhibit a broad spectrum of cardiac abnormalities. Myocardial injury is associated with a higher disease severity and risk of in-hospital mortality. This multicenter study uniquely represents data from 13 Latin American countries, offering regional insights into the impact of myocardial injury during the COVID-19 pandemic.